Petrocosmea panzhouensis (Gesneriaceae), a new species from Guizhou, China - Tang, Sheng-Hu; Zhang, Jian-Hua; Peng, Tao; Guo, Ying (Phytotaxa, 2022)
The two species with lobed leaves, viz., Petrocosmea henryi and P. weiyigangii are very distinctive from other species of Petrocosmea. Here, the third species with lobed leaves, named Petrocosmea panzhouensis, from western Guizhou, China, is described. The new species is most similar to P. henryi on shape of leaf blade margin and straight filaments, but it is distinguished from the latter by shape of bracts, and shape and length of anthers. The new taxon is assessed as “Data Deficient” (DD), according to the IUCN standards.